Taxonomy of the order Mononegavirales: update 2019 - Amarasinghe, Gaya K.; Ayllón, María A.; Bào, Yīmíng; Basler, Christopher F.; Bavari, Sina; Blasdell, Kim R.; Briese, Thomas; Brown, Paul A.; Bukreyev, Alexander; Balkema-Buschmann, Anne; Buchholz, Ursula J.; Chabi-Jesus, Camila; et al. (Archives of virology, 2019)
In February 2019, following the annual taxon ratification vote, the order Mononegavirales was amended by the addition of four new subfamilies and 12 new genera and the creation of 28 novel species. This article presents the updated taxonomy of the order Mononegavirales as now accepted by the International Committee on Taxonomy of Viruses (ICTV).